Kolaborasi Kampus dan Sekolah dalam Meningkatkan Literasi dan Numerasi melalui Edukasi Berbasis Teknologi - Sari, Rafika; Abdillah, Sabiq; Ayu, Visca Anindha; Agati DJ, Sharlen Taurisya; Manullang, Nathasya Grisella; Cahyani, Dwi Sinta; Novarizal, Safarin (Journal Of Computer Science Contributions (JUCOSCO), 2025)
The 8th Batch of the Kampus Mengajar Program at SMPN 5 Cikarang Utara aimed to improve students’ literacy and numeracy through collaborative and innovative approaches. Implemented activities included teaching assistance, weekly reading habits, educational programs such as "Word Puzzle" and "Numeracy Egg", revitalization of the school library and bulletin board, and the organization of a Literacy and Numeracy Festival. These activities not only targeted cognitive development but also fostered collaborative, creative, and competitive attitudes among students. The implementation method involved participatory collaboration among students, teachers, and university volunteers, while the evaluation was conducted through observations, student engagement levels, and post-test AKM (Assesmen Kompetensi Minimum) results. The program outcomes indicated an increase in student participation, the emergence of a reading culture within the school, and greater enthusiasm for learning. This article recommends sustaining such programs to support educational transformation at the junior high school level.